GCG, ROE and Size on CSR Based on Sharia Enterprises Theory - Dwi Nita Aryani; Imama Zuchroh (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
The purposes of this paper are to investigate the Corporate Social Responsibility (CSR) reporting information at Indonesia sharia banks based on Sharia Enterprise Theory and explores the potential effects of Corporate Governance (CG) elements, Return on Equity (ROE) on CSR based on sharia enterprises theory, with size as the moderating variable. Using the sample of 10 sharia banks which published annual reports, CG, and CSR reports above the year 2014 to 2016, the panel data are examined by regression. The statistic test reveals that size is not fit as a moderating variable in testing the effect of CG and ROE on CSR. Aggregately, GCG, Size and ROE influence CSR. A large and high-profit sharia bank which apply good corporate governance will implement CSR by considering horizontal and vertical accountability based on Sharia Enterprise theory. This study makes a significant contribution to the Corporate Social Responsibility (CSR) and enterprise theory by offering Sharia Enterprise theory as the foundation of the CSR implementation at sharia banks.